Pengaruh Model Pembelajaran Berbasis Proyek terhadap Kemampuan Menulis Karya Ilmiah Geografi Siswa SMA - Arif Baidowi; Sumarmi Sumarmi; Achmad Amirudin (Jurnal Pendidikan Geografi: Kajian, Teori, dan Praktek dalam Bidang Pendidikan dan Ilmu Geografi, 2015)
Abstract: The aim of this researchis to examine the effect of project-based learning model toward the writing ability of geography scientific papers on senior high school students.The subjects of the research are students of class XI IPS SMAN 1 Campurdarat consists of two classes. The both class are class XI IPS 1 as the control class and XI IPS 2 as experimentclass.The instrument is used to measure the ability to write scientific papers geography using the rubric of scientific papersassessment. Results were analyzed using independent samples t test with SPSS 20.0 for Windows.The results showed an average gain score of writing ability of geography scientific papers for experiment class is higher than the control class. The results of independent samples t test analysis showed that the project-based learning model significantly affect toward the writing ability of geography scientific papers on senior high school students.Keywords: Project-Based Learning, Writing Ability of  Geography Scientific  PapersDOI: http://dx.doi.org/10.17977/um017v20i12015p048